2021
DOI: 10.1016/j.mcpro.2021.100156
|View full text |Cite
|
Sign up to set email alerts
|

Pronounced Postmating Response in the Drosophila Female Reproductive Tract Fluid Proteome

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 114 publications
(234 reference statements)
3
22
0
Order By: Relevance
“…Although previous studies have identified individual proteins that bind to sperm (e.g., refs. 6 , 7 , 14 , 15 , 17 , and 20 ) and secreted proteins that are present or produced in the reproductive tracts of D. melanogaster females ( 34 38 ) and males (reviewed in ref. 39 ), there has been no comprehensive determination, in any organism, of the number, nature, and source of proteins that associate with sperm in the FRT.…”
mentioning
confidence: 99%
“…Although previous studies have identified individual proteins that bind to sperm (e.g., refs. 6 , 7 , 14 , 15 , 17 , and 20 ) and secreted proteins that are present or produced in the reproductive tracts of D. melanogaster females ( 34 38 ) and males (reviewed in ref. 39 ), there has been no comprehensive determination, in any organism, of the number, nature, and source of proteins that associate with sperm in the FRT.…”
mentioning
confidence: 99%
“…The molecular composition of the female reproductive tract has historically not received the same level of interrogation as the male ejaculate. Our analysis expands on a growing effort to characterise the female reproductive tract proteome (16, 19, 28, 56). Interestingly, the majority (> 90%) of D. melanogaster sperm protein orthologs we identified showed no difference in abundance between mated vs. virgin samples, suggesting expression in the female reproductive tract.…”
Section: Discussionmentioning
confidence: 99%
“…We compared protein abundances in the lower reproductive tracts of unmated females to those that were collected immediately after mating (thus containing ejaculate proteins) using tandem mass tag (TMT) labelled samples. Copulation duration in the virilis group is ~2 minutes and the majority of postmating female responses in Drosophila take place ~3 hours after the start of mating (20, 56), such that the female reproductive tract should remain in a “virgin-like” state.…”
Section: Introductionmentioning
confidence: 99%
“…Pavlovian conditioning may alter sperm rejection or it might also affect the composition of the female reproductive tract fluid, leading, in this particular case, to increased chances of successful insemination and lower costs for the male. In this regard, female reproductive tract fluid is much understudied, but there is very recent evidence showing that its composition changes after mating ( McDonough-Goldstein et al, 2021 ). It would thus be interesting to test whether Pavlovian conditioning could also alter the composition of females’ fluid, just as it changes seminal fluid in males.…”
Section: Introductionmentioning
confidence: 99%